Enhancing the translation of health behaviour change research into practice: a selective conceptual review of the synergy between implementation science and health psychology. Issue 1 (2nd January 2022) - Presseau, Justin; Byrne-Davis, Lucie M.T.; Hotham, Sarah; Lorencatto, Fabiana; Potthoff, Sebastian; Atkinson, Lou; Bull, Eleanor R.; Dima, Alexandra L.; van Dongen, Anne; French, David; Hankonen, Nelli; Hart, Jo; et al.
ABSTRACT: Health psychology is at the forefront of developing and disseminating evidence, theories, and methods that have improved the understanding of health behaviour change. However, current dissemination approaches may be insufficient for promoting broader application and impact of this evidence to benefit the health of patients and the public. Nevertheless, behaviour change theory/methods typically directed towards health behaviours are now used in implementation science to understand and support behaviour change in individuals at different health system levels whose own behaviour impacts delivering evidence-based health behaviour change interventions. Despite contributing to implementation science, health psychology is perhaps doing less to draw from it. A redoubled focus on implementation science in health psychology could provide novel prospects for enhancing the impact of health behaviour change evidence. We report a Health Psychology Review -specific review-of-reviews of trials of health behaviour change interventions published from inception to April 2020. We identified 34 reviews and assessed whether implementation readiness of behaviour change interventions was discussed. We then narratively review how implementation science has integrated theory/methods from health psychology and related discipline. Finally, we demonstrate how greater synergy between implementation science and health psychology could promote greater follow-through on advances made in the science of health behaviour change.